Does urbanization favour exotic bee species? Implications for the conservation of native bees in cities. (11th December 2019) - Fitch, Gordon; Wilson, Caleb J.; Glaum, Paul; Vaidya, Chatura; Simao, Maria-Carolina; Jamieson, Mary A.
Abstract : A growing body of research indicates that cities can support diverse bee communities. However, urbanization may disproportionately benefit exotic bees, potentially to the detriment of native species. We examined the influence of urbanization on exotic and native bees using two datasets from Michigan, USA. We found that urbanization positively influenced exotic—but not native—bee abundance and richness, and that this association could not be explained by proximity to international ports of entry, prevalence of exotic flora or urban warming. We found a negative relationship between native and exotic bee abundance at sites with high total bee abundance, suggesting that exotic bees may negatively affect native bee populations. These effects were not driven by the numerically dominant exotic honeybee, but rather by other exotic bees. Our findings complicate the emerging paradigm of cities as key sites for pollinator conservation.